Summarizing data for secure transaction: A hash algorithm - Basar, Mehmet Sinan (Academic Journals, 2011)
Hashing is a process of transforming a variable length data message into a fixed size message digest. Hashing algorithms are considered one-way functions, since the input cannot be determined from the message digests. As a security tool in data communication, hashing is used both for protecting data integrity and for authentication. This study introduces a newly developed hash function. In hashing function, the most important features required are that the function must hash a message of any size, a message with a fixed size, and minor changes formed in hashed message must also change the hash. Effects of possible deformations in the hash message will subsequently be discussed through some tests.
Keywords: Data Communication; Hashing Algorithms; Information Security; Electronic Commerce